2021
DOI: 10.3390/ijerph182212132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Congested Match Schedules, Pre-Match Well-Being and Level of Opponents on Match Loads during World Rugby Women’s Sevens Series

Abstract: This study aimed at assessing (1) the effect of congested match schedules on match loads and well-being as well as (2) pre-match well-being and level of opponents on match loads in elite women’s rugby sevens. Eleven players of the Brazilian women’s rugby sevens national team were investigated across three 2019-20 HSVC World Rugby Women’s Seven Series tournaments to assess: (1) within-tournament match-to-match changes in various external and internal match load measures; (2) daily changes in players’ well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…All these factors should be considered in future research using AROMs. On the other hand, we observed a very good methodological quality in many studies (Table 2), as well as robust numbers of data points collected, with only 3 studies with <100 observations (12,32,37).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…All these factors should be considered in future research using AROMs. On the other hand, we observed a very good methodological quality in many studies (Table 2), as well as robust numbers of data points collected, with only 3 studies with <100 observations (12,32,37).…”
Section: Discussionmentioning
confidence: 67%
“…Regarding match-related statistics (Table 3), 7 studies (14,25,37,38,49,52,55) found significant effects or associations, whereas 2 studies (46,48) did not find any effects or associations. For physical performance indicators (Table 4), 3 studies (19,28,32) found significant effects or associations, whereas 4 studies (3,12,14,29) did not find any effects or associations. Regarding perceived match demands (Table 5), 1 study (46) found effect or associations, whereas 1 study did not (12).…”
Section: Study Characteristics and Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Post-hoc analysis with Bonferroni correction was used in case of significant differences. All LMMs were analyzed using Jamovi software (the Jamovi project, version 2.3.3, 2022, Sydney, Australia, which was previously used in basketball research [ 9 , 16 ]. Available online: ).…”
Section: Methodsmentioning
confidence: 99%